Analisis Manajemen Risiko UMKM Rumah Donat di Lenteng Sumenep Berbasis ISO 31000: Identifikasi, Penilaian, dan Mitigasi - Firdaus, Jannatul; Khalida, Nur Diana; Arifah, Hertin Khalifatun Nisa; Najiatun, Najiatun; Hidayat, Nurul (MES Bogor, 2025)
Risk management plays a crucial role strategy for MSMEs because it can help them face operational challenges, minimize losses, and maintain business sustainability. This study aims to analyze risk management in Rumah Donat SMEs in Lenteng District, Sumenep, by adapting the ISO 31000 framework. The methods used are a qualitative approach through surveys, observations, in-depth interviews, and documentation. In addition, data analysis was carried out using the Miles & Huberman model combined with the preparation of a risk register and risk matrix. The results of the study identified four main risk categories, namely operational risks (increase in raw material prices, low product durability), strategic risks (limitations in digital promotion, seasonal market competition), human resource risks (lack of employee management), and natural and environmental risks (instability of raw material supply, power outages). Probability and impact analysis showed that seasonal market competition had the highest level of risk, followed by limitations in digital promotion. The proposed mitigation recommendations included establishing cooperation with suppliers, product innovation, employee training, expanding online marketing, improving business management, and developing a framework to address environmental risks. The study seeks to provide valuable contributions to theory as well as practical guidance for MSMEs in managing risks effectively and efficiently.